The Effect Of State Capital Participation On The Financial And Non-Financial Performance Of State-Owned Enterprises And Other Institutions - Yudha Abimanyu; Rofikoh Rokhim (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Researchers conducted an empirical study to examine state equity participation and additional paid-in capital for control companies on their effect on financial performance represented by ROA, ROE, DAR, and DER as well as non-financial performance measured by CSR funds. This study was conducted to see if there were differences before and after the company received PMN or additional paid-in capital. This study uses 20 experimental companies consisting of state-owned enterprises and 20 control companies which are private companies going public with the same sector as the experimental companies. The results showed that state equity participation in SOEs as experimental companies and additional paid-in capital had no effect on the company's financial performance as well as non-financial performance. This can be caused by several influencing factors. These results are also important for company management so that they can be used as a consideration in making strategic policies so that PMN or additional paid-in capital can have a positive influence on the company's financial performance and non-financial performance.